PROTEIN SOLUBLE SUPPRESSION OF TUMORIGENICITY 2 (sST2) SEBAGAI PENANDA KERUSAKAN KARDIOVASKULAR PADA PREEKLAMSIA - Laksmi Maharani (Fakultas Kedokteran Universitas Trisakti, 2024)
Preeclampsia as a pregnancy complication was still a direct cause of maternal death, especially in developing countries. The process of abnormal trophoblast invasion as a pathophysiology of preeclampsia would cause an ischemic environment in the placenta. This situation caused the placenta to release pro-inflammatory cytokines and anti-angiogenic factors into the maternal circulation, resulting in the vasocontriction of blood vessels, endothelial dysfunction in the vasculature of maternal organs, and the production of different clinical features depending on the organs affected. Vascular and myocardial muscle damage was a complication that causes cardiovascular disorders and could increase maternal morbidity and mortality in preeclampsia. sST2 as part of the interleukin (IL)-1 receptor, was a biomarker used to indicate myocardial muscle damage in cardiac disease. There had been a growing number of research investigating the use of sST2 as a marker of cardiac muscle damage in patients with heart failure. Some of them concluded that sST2 can be used as a predictor of acute cardiac muscle damage. Others stated that sST2 as a marker could accompany chronic cardiac defects. Preeclampsia, as a disease in pregnancy that showed damage to maternal organs, was starting to be studied using this biomarker as a marker for damages to the cardiac organ. There were studies that showed differences in sST2 levels in preeclampsia with and without complications. Preeclampsia with cardiac complications was characterized by damage to the myocardial muscle, especially to the left ventricular area. The sST2 protein was starting to be used as a marker for this damage. Further research was still being carried out to improve the use of this biomarker as a marker for other damage to the maternal cardiac organ.